Evasão escolar no ensino médio noturno: mediações entre as políticas educacionais contemporâneas e as dinâmicas escolares - Lopes, Bernarda Elane Madureira (2017)
This study seeks to understand school drop outs in the Regular Evening Secondary Education, having in sight the complexity and the multiform nature of this phenomenon, and the context historical, social, economic and political in which the students are at this stage. With this in sight, there is an analysis of intermediate mediation of public education policies for Secondary Education and the prolonging of school drop outs. Having school drop outs as a focus of the study, the general objective presented is to understand the factors which contribute to school drop outs in the regular Secondary public schools of the municipality of Montes Claros, Minas Gerais, in the period between 2010 and 2013, analyzing the school world and its interface with its context: social, economic and political in the macro-social and micro-social dimensions. This survey consists of a qualitative investigation, structured as a Case Study, using these techniques: interview with school drop outs, a teacher’s questionnaire, field notebook and document analysis. The information gathered was subject to content analysis to construct the results of this study. Collected data was analyzed in light of relative theoretical contributions, the public educational policies for Secondary Education, and of authors who conceptualize school drop out and discuss the juvenile condition of this age group. This thesis defends that the factors which contribute to school drop outs in Regular Evening Secondary Education have a direct link to the contexts social, economical and political in the macro-social and micro-social dimensions. It also defends, that there does not exist a perception, on the student’s part, that questions: micro-social, micro-social, internal and external, to the school could contribute to dropping out at this stage of learning. Furthermore, there does not exist a specific public educational policy, external or internal to guarantee and motivate students to remain in school at this stage of learning. The results show the same for students as for teachers that the factors that contribute to dropping out are related to internal and external questions at the school, including macro-social and micro-social aspects. Soon, macro-social aspects are linked to work, teen pregnancy; and the micro-social allude to factors linked to curricular organization, methodology, physical structure of schools and both to the precariousness of teaching. These factors reflect social, economic and political conditions of Brazilian society. In addition, the majority of former students attribute dropping out to themselves and personal motives. A great number of teachers associate students dropping out to the need to work. Facing the situation of Brazilian Secondary Education, in what is referred to as studied phenomenon, the contributions of this work concentrate in the visibility of factors that cause student drop outs during Secondary Education. With this bias, it is noticed, also, a lack of effective public educational policies that appreciate the condition of the youth and contribute to students remaining in school. To you, it is desired that such visibility could contribute to rethinking educational policies pedagogical practices for regular Evening Secondary Education in the country.